Case Report: Pemphigus in Young Patients With Thymic Anomalies - Lin, Naiyu; Li, Xiaoli; Lang, Yuejiao; Han, Jiande (Frontiers in Medicine, 2022)
Pemphigus is an autoimmune disease that occurs mainly in elderly individuals. Young patients with pemphigus are rare, and the risk factors are unclear. The thymus is associated with a variety of autoimmune diseases, and there have been reports of pemphigus complicated with thymic diseases. Here, we report three cases of young patients with pemphigus that were associated with thymic anomalies. We suggest that thymic anomalies may be a risk factor for the early onset of pemphigus and may be associated with increased severity of the disease. Interventions for thymic diseases have certain benefits for improving the effect of treatments and prognosis of these patients.